İnsani yardım kuruluşlarının marka imajı ile bu kurumlara olan bağlılık ve dini ilgilenimin bağışta bulunma niyetine etkisi - Yapraklı, Tevfik Şükrü; Ünalan, Musa (My University, 2016)
Bu araştırmanın amacı kar amacı gütmeyen insani yardım kuruluşlarının marka imajı ile bu kuruluşlara olan bağlılık ve dini ilgilenimin bağışta bulunma niyetine etkisini incelemektir. Marka imajı, tüketicinin markaya karşı hissettiği duygu ve düşüncelerin toplamıdır. Bağlılık, güven duygusu içerisinde kurum ile olan ilişkiyi uzun vadeli yürütmektir. Dini ilgilenim ise bireylerin ve toplumun değer ve tutumlarında önemli bir rol oynayan etkileyici bir unsurdur. Bu çalışma Erzurum il sınırlarında yaşayan katılımcılara uygulanmış olup 412 anket değerlendirmeye alınmıştır. Verilerin analizinde SPSS 20 istatistik programı kullanılmış olup, anketi cevaplayanların demografik özellikleri de incelenmiş ve faktör analizi, güvenilirlik testleri, t-testi ve regresyon analizleri yapılmıştır. Bağışta bulunmada marka imajı ve bağlılığın etkisinin olduğu, dini ilgilenimin etkisinin ise olmadığı bulunmuştur. The purpose of this study is to examine the effects of brand image of humanitarian aid organizations, commitment to these organizations and religious involvement on the intention to donate. Brand image is a function of what consumers feel and think about brand. Commitment is about maintaining long term relations with an organization through a feeling of trust. Religious involvement is an important factor influential on personal and societal values and attitudes. The research utilizes survey method and data from 412 participants in Erzurum Province of Turkey are used to test the research hypotheses. The collected data is analyzed by SPSS 20 software package through descriptive, frequency, factor analysis, reliability tests and regression analysis. The findings of the study show that brand image and commitment have a significant effect on charitable giving whereas the effect of religious involvement is non-significant.

The purpose of this study is to examine the effects of brand image of humanitarian aid organizations, commitment to these organizations and religious involvement on the intention to donate. Brand image is a function of what consumers feel and think about brand. Commitment is about maintaining long term relations with an organization through a feeling of trust. Religious involvement is an important factor influential on personal and societal values and attitudes. The research utilizes survey method and data from 412 participants in Erzurum Province of Turkey are used to test the research hypotheses. The collected data is analyzed by SPSS 20 software package through descriptive, frequency, factor analysis, reliability tests and regression analysis. The findings of the study show that brand image and commitment have a significant effect on charitable giving whereas the effect of religious involvement is non-significant
The effect of humanitarian aid organizations brand image, commitment to these organizations and religious involvement on the intention to donate
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Yardım kuruluşları; Marka imajı; Bağlılık; Dini ilgilenim; Bağışta bulunma niyeti; Charitable organizations; Brand image; Commitment; Religious involvement; Intention to donate